Project work: the legacy of bureaucratic control in the post-bureaucratic organization - Hodgson, Domian E. (2004)
Much of the interest in `post-bureaucracy' in both managerialist and critical circles resides in its perceived potential to break with the traditions of bureaucratic, hierarchical control in work organizations. In response to the challenges of the post-bureaucratic form, project management has been put forward by many as a `tried-and-test' package of techniques able to cope with discontinuous work, expert labour and continuous and unpredictable change while delivering the levels of reliability and control of the traditional bureaucracy. In this article I explore some of the contradictions and tensions within a department where such a `hybrid' mode of control is implemented, embodying both bureaucratic and post-bureaucratic logics. In particular, I focus upon the discursive tactics employed to sell `rebureaucratization' as `debureaucratization', and the complex employees responses to this initiative. I argue that the tensions evident here cast significant doubt on the feasibility of a seamless integration of bureaucracy and the post-bureaucratic. - Reproduced.
Keywords: Project management; Bureaucracy